Rare variants in known and novel candidate genes predisposing to statin-associated myopathy - Neřoldová, Magdaléna; Stránecký, Viktor; Hodaňová, Kateřina; Hartmannová, Hana; Piherová, Lenka; Přistoupilová, Anna; Mrázová, Lenka; Vrablík, Michal; Adámková, Věra; Hubáček, Jaroslav; Jirsa, Milan; Kmoch, Stanislav (Pharmacogenomics, 2016)
AIM: Genetic variants affecting statin uptake, metabolism or predisposing to muscular diseases may confer susceptibility to statin-induced myopathy. Besides the SLCO1B1 rs4149056 genotype, common genetic variants do not seem to determine statin-associated myopathy. Here we aimed to address the potential role of rare variants. METHODS: We performed whole exome sequencing in 88 individuals suffering from statin-associated myopathy and assessed the burden of rare variants using candidate-gene and exome-wide association analysis. RESULTS: In the novel candidate gene CLCN1, we identified a heterozygote truncating mutation p.R894* in four patients. In addition, we detected predictably pathogenic case-specific variants in MYOT, CYP3A5, SH3TC2, FBXO32 and RBM20. CONCLUSION: These findings support the role of rare variants and nominate loci for follow-up studies.
Keywords: dospělí; Rare Diseases; senioři nad 80 let; polypeptid C přenášející organické anionty; Humans; lidé středního věku; Muscular Diseases; Middle Aged; Aged, 80 and over; Genotype; celogenomová asociační studie; genetická variace; Exome; mužské pohlaví; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Adult; statiny; exom; Liver-Specific Organic Anion Transporter 1; Chloride Channels; ženské pohlaví; Genetic Variation; genotyp; lidé; chloridové kanály; Genome-Wide Association Study; nemoci svalů; Aged; senioři; Male; vzácné nemoci; Female